Nurse Staffing, Work Hours, Mandatory Overtime, and Turnover in Acute Care Hospitals Affect Nurse Job Satisfaction, Intent to Leave, and Burnout: A Cross-Sectional Study - Bae, Sung-Heui (International Journal of Public Health, 2024)
Objectives. This study examined the impact of nurse staffing, working hours, mandatory overtime, and turnover on nurse outcomes in acute care hospitals. Previous studies have focused on the single characteristics of sub-optimal nurse staffing but have not considered them comprehensively. Methods. Data were collected in July–September 2022 using convenience sampling and an online survey (N = 397). For the analysis, 264 nurses working as staff nurses at 28 hospitals met the inclusion criteria. Univariate analysis and multivariable generalized estimating equation (GEE) were performed. Results. Both nurse staffing (β = -0.036, standard error [SE] = 0.011) and turnover (β = -0.006, SE = 0.003) were significant factors affecting job satisfaction. In the multivariable GEE, only mandatory overtime (β = 0.395, SE = 0.116) was significantly related to intent to leave. Nurse staffing, work hours, mandatory overtime, and turnover were not significantly related to burnout. Subjective health status and workload were significantly associated with burnout. Conclusions. Nurse staffing policies and improvement programs in hospitals should be implemented to improve nurses’ job satisfaction. Labor policy should ban mandatory overtime.